Cytokines and Inflammatory Mediators in Systemic Lupus Erythematosus (2018)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterised by a breakdown in immune tolerance that induces an attack on normal tissues by the immune system. The dysfunction within both the innate and adaptive immune systems increases cytokine production, B lymphocytic overproduction of autoantibodies, and T lymphocyte activity. Cytokines and inflammatory mediators have been associated with several clinical endpoints, including the activity of disease and outcomes. In fact, some of them have been associated with different clinical subphenotypes (e.g., lupus nephritis), suggesting their role as biomarkers, and, in some cases, therapeutic targets. Thus, knowledge of the pathophysiological processes associated with the development of SLE could aid in setting up better diagnostic and therapeutic approaches to reduce the high burden of disease, and thus improve quality of life and outcomes. Herein, the authors have compiled a concise review of the clinically relevant cytokines and inflammatory mediators associated with SLE and its manifestations.